Factors Analysis Influencing on Demand for Private Health Insurance in Indonesia After Pandemic - Putri Agustin, Sartika; Tunom, Sajun; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2023)
The study focused on the purpose of this writing is to find out the importance of today's health insurance such as protection for yourself and your family, by having health insurance you and your family will get health protection. If at any time you need treatment and medication, insurance will cover these needs. Sickness is an unexpected event that can happen to anyone, including yourself and your family. Therefore, with the protection you get from insurance, you will be calmer in living your life and not confused if you must spend large funds for medical needs. This study uses qualitative research methods, which are related to the subject and research informants. Private health insurance in Indonesia still has an important role to play in protecting individuals and families from the financial risks associated with health care costs. The demand for private health insurance is influenced by several complex and varied factors. An analysis of the factors affecting the demand for private health insurance in Indonesia will be important after the pandemic is over. Through a better understanding of these factors, the government and the private sector can make policy decisions in designing appropriate strategies to improve the accessibility, sustainability, and quality, of private health insurance.